The relationship between input factors and early lexical knowledge in Turkish-German children - Budde-Spengler, Nora; Sachse, Steffi; Rinker, Tanja (International journal of bilingual education and bilingualism, 2021)
Lexical development of bilingual children is influenced by a number of input factors. In the present study, early lexical skills of 25-month old children growing up with Turkish and German were assessed. Parents of 92 children filled out a newly developed list for productive Turkish vocabulary, as well as a vocabulary list for German. A parental questionnaire served to examine the quality and quantity of familial and extra-familial language input. The results showed that children who grow up in a predominantly Turkish-speaking environment subsequently have a larger Turkish vocabulary than German vocabulary. More German input within the family was shown to lead to higher vocabulary scores, but not to a reduction of Turkish vocabulary at this age. Factors predicting vocabulary in both languages included parental language quality and quantity, as well as the number of available books and childcare.